Social movement, public policy changes and partnerships building for local development - Vasconcellos, Mário (2016)
The paper debates the rural social movement’s infl uence on policy changes for small-scale rural producers and the creation of partnerships between Government and Local Organizations for local development in Amazonia, particularly in Pará state. The paper’s goal is to examine partnership as a result of an interactive process of both changes of public policies and the demands of social movements. The paper shows that although social movements are part of a relation of conflict between state and society, in Pará they were a precondition for changes in public policy, financing and in the priorities of regional agencies that resulted in propositions for cooperation between local Government and Local Organizations at município level